Project-Based Learning Model to Improve Students' Understanding and Critical Thinking Skills in Islamic Education Learning - Yuneiti (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve students' conceptual understanding and critical thinking skills in Islamic religious education learning using project-based learning models. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure the results of students' conceptual understanding and critical thinking skills, while observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that project-based learning models can improve students' conceptual understanding and critical thinking skills in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 58.61%, the first cycle 76.57% and in the second cycle it increased to 93.31%. Thus, the use of project-based learning models can be used as an alternative to improve students' conceptual understanding and critical thinking skills in Islamic religious education learning.